Association of Serum Uric Acid Levels in Patients with Acute Ischemic Stroke and Clinical Outcome (TAJ: Journal of Teachers Association, 2022)
Background: Stroke is one of the most common, most fatal, and debilitating neurologic diseases. Numerous risk factors are involved in the development of strokes, such as hypertension, cigarette smoking, hyperlipidemia, and diabetes. In addition, other factors may influence the disease's development or course, like uric acid serum level.Objective: To determine the association between serum uric acid (SUA) levels in patients with acute ischemic stroke and clinical outcomes.Material and method: This was a longitudinal descriptive study carried out among one hundred and twenty consecutive patients with acute ischemic stroke (AIS) admitted to the Department of Neuromedicine, Rajshahi Medical College Hospital ( during a period of two years from July'2015 to July' '2017 were included in the study.  12.11 years. Of 120 patients with AIS, 60.8% were male, and 39.2% were female. The study revealed that AIS patients with high SUA levels have significantly lower Glasgow Coma Scale (GCS) scores in comparison to normal SUA levels (p